2020
DOI: 10.4252/wjsc.v12.i9.897
|View full text |Cite
|
Sign up to set email alerts
|

Dental stem cells: The role of biomaterials and scaffolds in developing novel therapeutic strategies

Abstract: Dental stem cells (DSCs) are self-renewable cells that can be obtained easily from dental tissues, and are a desirable source of autologous stem cells. The use of DSCs for stem cell transplantation therapeutic approaches is attractive due to their simple isolation, high plasticity, immunomodulatory properties, and multipotential abilities. Using appropriate scaffolds loaded with favorable biomolecules, such as growth factors, and cytokines, can improve the proliferation, differentiation, migration, and functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 245 publications
1
38
0
Order By: Relevance
“…Increased survival and migration of engrafted hNS/PCs in PM could be due to significantly improved biocompatibility and integration with the host tissue, which promotes the regeneration of damaged spinal cord tissue [24,39]. Hydrogel scaffolds play a shielding role against the host immune system and exhibit anti-gliosis and anti-inflammatory properties when fused with host tissue [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Increased survival and migration of engrafted hNS/PCs in PM could be due to significantly improved biocompatibility and integration with the host tissue, which promotes the regeneration of damaged spinal cord tissue [24,39]. Hydrogel scaffolds play a shielding role against the host immune system and exhibit anti-gliosis and anti-inflammatory properties when fused with host tissue [42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…Although stem cells are widely used in regenerative medicine, most of the preclinical and clinical studies demonstrated a poor functional integration into the host tissue, so several 3D scaffold-based cultures have been developed [ 9 , 12 , 28 , 58 , 59 , 60 , 61 , 62 , 165 ]. Stem cell 3D cultures are not without limitations; however, they enhance cell growth, differentiation, migration and improve cellular communications [ 21 , 166 ]. According to some authors, complete damage tissue regeneration might be achieved by using an appropriate scaffold, or associated with favorable biomolecules, such as growth factors, cytokines and combined with dental-MSCs [ 9 , 21 , 166 ].…”
Section: Dental-mscs and Their Secretome Combinated With Scaffold In Regenerative Medicinementioning
confidence: 99%
“…Stem cell 3D cultures are not without limitations; however, they enhance cell growth, differentiation, migration and improve cellular communications [ 21 , 166 ]. According to some authors, complete damage tissue regeneration might be achieved by using an appropriate scaffold, or associated with favorable biomolecules, such as growth factors, cytokines and combined with dental-MSCs [ 9 , 21 , 166 ]. Two main approaches for this combination are cell-based and cell-free tissue engineering.…”
Section: Dental-mscs and Their Secretome Combinated With Scaffold In Regenerative Medicinementioning
confidence: 99%
“…In this context, the main purpose of regenerative medicine is to overcome the limit of the low regenerative power of tissues, creating strategies to restore their functionality and architecture. Tissue engineering denotes a novel approach to regenerative medicine in order to develop tissue-like complexes that mimic the role and structural organization of tissues in order to repair injuries, anatomical defects, and restore the functions of the damaged areas using biomaterials and stem cells [ 3 , 4 , 5 ]. Specifically, the differentiation capacity and the paracrine effects of stem cells, such as mesenchymal stem cells (MSCs), are useful for tissue regeneration, and their application seems promising in different fields of regenerative medicine, including bone regeneration [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%